Annotated catalogue of type specimens of Iberian Leptodirini Lacordaire, 1854 (Coleoptera: Leiodidae: Cholevinae) deposited in the Natural Science Museum of Barcelona (Spain) - Prieto-Manzanares, Miguel; Masó-Ros, Glòria (Zootaxa, 2025)
An annotated catalogue of the type specimens of the Iberian Leptodirini (Coleoptera: Leiodidae: Cholevinae) deposited in the entomological collection of the Natural Science Museum of Barcelona is presented. This type collection represents the fruits of the biospeleological work carried out by the Museum from the first third of the twentieth century onwards, which focuses above all on the taxonomy and faunistic studies of subterranean beetles. In addition to the material collected by entomologists linked to the Museum, this collection also houses type specimens donated by other specialists and institutions, from within and outside the Spanish state. Most of the type specimens are hypogean species originating largely from the north and northeast of the Iberian Peninsula, with a prevalence of specimens from the Pyrenean, Catalan and Cantabrian biospeleological regions. As of the end of 2023, this type collection consists of 3807 specimens grouped in 1339 registers. In all, the 142 described taxa belong to 26 valid genera, of which Quaestus Schaufuss, 1861 and Troglocharinus Reitter, 1908 are the best represented. The information associated with the Museum’s type series includes type category, type locality, number of specimens, register numbers in the collection, current accepted name, and remarks. Photographs of type specimens representative of the collection are also provided (generally for taxa described by older authors or not illustrated previously).